2006
DOI: 10.1007/s10753-006-9003-1
|View full text |Cite
|
Sign up to set email alerts
|

“In Vitro” Differences among (R) and (S) Enantiomers of Profens in their Activities Related to Articular Pathophysiology

Abstract: An important group of non steroidal antinflammatory drugs (NSAIDs), which have been used for the symptomatic treatment of various forms of arthritis, are the 2-arylpropionic acid derivatives, 'profens'. By virtue of a chiral carbon atom on the propionic acid side chain, they exist as enantiomeric pairs. Whereas the S (+) enantiomer could be represented as an effective, but unselective COX inhibitor, the R (-) enantiomer could be much less active in this respect. However, recent findings suggest that certain ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…This effect is in accordance with the expected function of active isomer of profens on COX enzymes 2,21,24 . No effect of S-(þ)-ibuprofen at 50 mM on reduction of NO synthesis and proteoglycans degradation was found in contradiction with results obtained for active isomer of ketoprofen and S-(þ)-flurbiprofen which reduced at 10 mM the synthesis of NO from human chondrocytes treated with IL-1 24 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This effect is in accordance with the expected function of active isomer of profens on COX enzymes 2,21,24 . No effect of S-(þ)-ibuprofen at 50 mM on reduction of NO synthesis and proteoglycans degradation was found in contradiction with results obtained for active isomer of ketoprofen and S-(þ)-flurbiprofen which reduced at 10 mM the synthesis of NO from human chondrocytes treated with IL-1 24 .…”
Section: Discussionsupporting
confidence: 90%
“…Clinically, use of single active isomer of the profens class of NSAIDs instead of the racemate mixture may represent a reduction of dose during treatment leading to a less exposition to xenobiotics and a reduction of renal load 23 . In vitro, biological activities of several NSAIDs isomers on joint cells were analyzed: S-(þ)-ketoprofen and S-(þ)-flurbiprofen on human chondrocytes treated with interleukin-1 24 and carprofen isomers on equine chondrocytes and synoviocytes after lipopolysaccharides (LPS) treatment 25,26 . No such study was undertaken for S-(þ)-ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, ASA, but not indomethacin or acetaminophen inhibits cytokine-induced nitrite production in cardiac fibroblasts [95]. Furthermore, there was no significant difference between the S- and R- pure enantiomers of flurbiprofen and ketoprofen as regards the reduction of NO release from IL-1β stimulated human chondrocytes [96], and exogenous PGE 2 did not reverse the inhibitory effects of celecoxib on NO production by activated human articular chondrocytes [97]. …”
Section: Non-opioids and Nitric Oxidementioning
confidence: 99%
“…The use of the pure enantiomers of flurbiprofen and ketoprofen can help answer this question, since the S-enantiomer inhibits PGE 2 synthesis, while the R-enantiomer is devoid of this property. Panico et al [96] showed in human chondrocytes that S-flurbiprofen and Sketoprofen inhibits IL-1β induced MMP-3 production to a greater extent than R-flurbiprofen and R-ketoprofen. However, R-flurbiprofen and R-ketoprofen significantly inhibited IL-1β induced MMP-3 production, suggesting that inhibition of PGE 2 production, though participating in this process, is not the sole player.…”
Section: Possible Factors Contributing To Non-opioids Effects On Mmpsmentioning
confidence: 99%